Survey: Transformer based video-language pre-training - Ludan Ruan; Qin Jin (AI Open, 2022)
Inspired by the success of transformer-based pre-training methods on natural language tasks and further computer vision tasks, researchers have started to apply transformer to video processing. This survey aims to provide a comprehensive overview of transformer-based pre-training methods for Video-Language learning. We first briefly introduce the transformer structure as the background knowledge, including attention mechanism, position encoding etc. We then describe the typical paradigm of pre-training & fine-tuning on Video-Language processing in terms of proxy tasks, downstream tasks and commonly used video datasets. Next, we categorize transformer models into Single-Stream and Multi-Stream structures, highlight their innovations and compare their performances. Finally, we analyze and discuss the current challenges and possible future research directions for Video-Language pre-training.